2021
DOI: 10.1021/acs.macromol.1c00107
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Solvatochromism of Polydiacetylenes Based on Extensively Hydrogen-Bonded Tubular Arrays

Abstract: Since the pioneering discovery by Wagner, polydiacetylenes (PDAs) and their solvatochromic properties (typically blue-to-red or purple transitions) have been the subject of extensive research efforts. Without exception, PDAs have been found to undergo irreversible solvent-induced color changes, and no cases exist in which initial blue states of the PDAs are regenerated after solvent removal. Herein, we describe the first example of a reversibly solvatochromic PDA that is derived from a macrocyclic diacetylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…A presumptive understanding from earlier reports including those from our lab for solvatochromism is that the color changes are a consequence of the dissolution of unpolymerized residual DA monomers that creates structural cavities in the PDA supramolecular structure and thus results in partial distortion of the π-conjugated backbone . Surprisingly, MCDA-Ni monomers with good solubility in CHCl 3 and CH 2 Cl 2 did not show any colorimetric change at MCPDA-Ni .…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…A presumptive understanding from earlier reports including those from our lab for solvatochromism is that the color changes are a consequence of the dissolution of unpolymerized residual DA monomers that creates structural cavities in the PDA supramolecular structure and thus results in partial distortion of the π-conjugated backbone . Surprisingly, MCDA-Ni monomers with good solubility in CHCl 3 and CH 2 Cl 2 did not show any colorimetric change at MCPDA-Ni .…”
Section: Resultsmentioning
confidence: 74%
“…The easy processability of the PDAs makes them suitable for designing devices in different shapes. In general, PDAs display irreversible colorimetric behavior with blue-to-red color transition, and very few PDAs undergo a reversible color change in response to external stimuli. Most of the PDAs with reversible chromatic behavior are caused by heat. In our very recent study, we demonstrated the first example of reversibly solvatochromic PDA derived from a tetracarboxylic acid-substituted macrocyclic diacetylene (MCDA) that has an extensively hydrogen-bonded network of tubular arrays …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This design concept offers an advantage when applied to macrocyclic DA monomers, which first undergo supramolecular assembly and then UV-induced cross-linking to generate a structurally stable covalently connected tubular morphology. Typical organic-based nanotubes are responsive to environmental conditions and can deform easily due to noncovalent molecular interaction-promoted assemblies. Results from our studies demonstrate that macrocyclic diacetylenes (MCDA) undergo self-assembly that is enforced by multiple interactions, including a π–π interaction from the acetylenic template, to form perfectly aligned stacks with a favorable polymerizable geometry, which transform into a covalently linked polymer structure via UV-induced polymerization. …”
Section: Introductionmentioning
confidence: 95%